Hyphessobrycon uaiso: new characid fish from the rio Grande, upper rio Paraná basin, Minas Gerais State (Ostariophysi: Characidae), with a brief comment about some types of Hyphessobrycon - Carvalho, Fernando R.; Langeani, Francisco (Sociedade Brasileira de Ictiologia, 2013)
Hyphessobrycon uaiso é descrito da bacia do alto rio Paraná, drenagem do rio Grande, Minas Gerais. A espécie nova difere de seus congêneres por apresentar nadadeira anal curta, com 12-17 raios ramificados, e nadadeira dorsal com ii,7-8 raios. Além disso, a espécie nova pode ser distinguida pelo número de raios da nadadeira pélvica, com i,5-6 e padrão de colorido do olho (quando vivo), levemente azulado na parte inferior e escurecido na parte superior. Ocorrências novas de Hyphessobrycon são registradas para a bacia do alto rio Paraná: H. eilyos Lima & Moreira, H. guarani Mahnert & Géry e H. herbertaxelrodi Géry. O estado da arte da ictiofauna da bacia do alto rio Paraná e comentários sobre alguns exemplares-tipo de Hyphessobrycon são discutidos brevemente.

Hyphessobrycon uaiso is described from the upper rio Paraná basin, rio Grande drainage, Minas Gerais State. The new species differs from its congeners by the short anal fin with 12-17 branched rays, and dorsal fin with ii,7-8 rays. Besides, it can be distinguished by the presence of i,5-6 pelvic fin rays, and by the coloration of the eyes (in life), slightly blue on the lower half and blackish on the upper half. New records of Hyphessobrycon are recognized for the upper rio Paraná basin: H. eilyos Lima & Moreira, H. guarani Mahnert & Géry, and H. herbertaxelrodi Géry. The knowledge status about the ichthyofauna from the upper rio Paraná basin and comments about the type material of some species of Hyphessobrycon are briefly discussed.
Keywords: Characiformes; Conservation status; Headwaters; New records; Systematics